If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(4c + -8) + 2c = 36 Reorder the terms: 0.5(-8 + 4c) + 2c = 36 (-8 * 0.5 + 4c * 0.5) + 2c = 36 (-4 + 2c) + 2c = 36 Combine like terms: 2c + 2c = 4c -4 + 4c = 36 Solving -4 + 4c = 36 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4c = 36 + 4 Combine like terms: -4 + 4 = 0 0 + 4c = 36 + 4 4c = 36 + 4 Combine like terms: 36 + 4 = 40 4c = 40 Divide each side by '4'. c = 10 Simplifying c = 10
| 8x-(3x+4)=x-28 | | 5(7x-8)=40-5x | | 15+c-3=24 | | -3v-9=-(v+1) | | -99=-7n+5(1+4n) | | N=2n-15 | | 27x^2+189x=0 | | n-(-17)=26 | | 2n-2(2n-6)=4-4n | | 34=6+2(p+5) | | 27x^2+189=0 | | a^3-3a^2-16a+48=0 | | 5a+2(a-1)=61 | | 1/4(8d-4)=-4d-7 | | -11+7V=8(1-2V)+4V | | 6(y-3)+y=38 | | 20x^3+30x=0 | | 12-a(a+1)=0 | | w^2+6x+8=0 | | 46-8x=6(1-8x) | | 3(2+4a)=54 | | 45x^2+380x+160=0 | | X-35=46 | | 12-a(a-1)=0 | | 6(4+5p)=-186 | | 3(x-4)+x=32 | | -0.8(5x-10)=16 | | 5x-10=6x+15 | | 6(e-1)=4.4e-2 | | N^2-18n=40 | | y-12=-25 | | T=3s+4.14 |